The Individual in the Economic and Monetary Union - Bobić, Ana (Cambridge University Press, 2024)
The European Union's response to the financial crisis was designed in a way that prevented EU citizens from holding decision-makers accountable. This book reimagines legal accountability by focusing on the citizen, who should be at the centre of the common interest in the EU, with solidarity and equality as guiding principles.